EFFECT OF PRODUCTION STRATEGY PERFORMANCE ON BRAND ROYALTY - Zaelani Adnan, Ahmad; Dedy Kurnaendar; Eeng Ahman; Disman Disman; Tjutju Yuniarsih (Dinasti International Journal of Management Science, 2022)
A product strategy or product strategy is a plan that identifies the aims and objectives of a product and then describes a vision for achieving these goals. It helps link the project's vision to the actual methods used to implement it. A product strategy maps out the critical benchmarks against the creation, marketing, and distribution of any concept you plan to sell. They also provide a central plan that people can refer to guide their efforts and refine their overall business strategy. The food business is a potential business at this time. Factors that need to be considered in facing competition in the restaurant business include product and price. If these two factors are getting better and more attractive, it can make customers feel satisfied. If customers are satisfied, they will be loyal to the restaurant. This study aimed to determine the effect of the performance of the production strategy on brand royalties in companies and restaurants